Mahasiswa Mandailing dan Kesadaran Identitas Etnik Pasca Pemilihan Presiden 2019 di Kota Medan - Armansyah Matondang (Universitas Negeri Medan, 2021)
This study aims to determine how the awareness of Mandailing Students towards their ethnic identity and how the role of mother's communication in instilling the values of Mandailing identity from an early age. The research approach was carried out qualitatively, data was obtained through literature study, observation, in-depth interviews and documentation. The results showed that the young Mandailing generation had a low level of awareness and understanding of the ethnic existence they carried. This condition applies because there is no information inheritance from parents, relatives regarding ethnic identity and it is not taught at school.